The idiomatic amplitude of Spain: Paradise or Averno if it is used politically? - Javier Manso Vergara (Ибероамериканские тетради, 2017)
Nowadays, in Spain, the use of the regional co-ofﬁcial languages as a barrier and linguistic weapon is supporting the idea of independence of some autonomous communities and to the detriment of the rest of the spaniards. We speak about a brief immersion in this topic, even quoting verses of the Bible, for an explication of the use of language as a political weapon and the damages it makes.